Biomimetic Approaches for Membrane Technologies. Issue 2 (2nd April 2016) - Sengur-Tasdemir, Reyhan; Aydin, Sevcan; Turken, Turker; Genceli, Esra Ates; Koyuncu, Ismail
Abstract : Membrane technology is the dominant process in water treatment. However, the operation cost of membranes cannot be decreased unless the amount of fouling, the "Achilles heel" of membranes, and energy consumed are cut. The high energy requirements in commercial nanofiltration, reverse osmosis and forward osmosis technologies lead researchers to develop new membrane designs having high flux values with high salt rejection values. The purpose of this review is to present the inadequacies of the membrane processes by considering studies related to fouling and energy minimization. In this respect, lipid bilayers, block copolymers, aquaporin Z proteins and aligned carbon nanotubes can be the base to build biomimetic membranes. Such studies are summarized due to their remarkable properties in fouling control. Furthermore, the review describes the membrane design strategies and points the limitations hindering commercialization. Additionally, it is hoped that this review will trigger further needed studies.